Pokroky ve vývoji vakcín proti HIV, tuberkulóze a malárii - Grznárová, Petra; Lipov, Jan (Chemické listy, 2010)
The research in vaccine development is growing very intensively. More than 95 clinical trials of potential HIV vaccines have been performed in last 25 years. Currently, only two HIV vaccine candidates are in Phase III trials and one in Phase II trial. Tuberculosis is another problematic disease of the 21st century. Calmette-Guérin vaccine from Mycobacterium bovis bacillus is the only one used for immunization against tuberculosis. Unfortunately, it is effective only in newborns but not in adults; thus, efforts are still put to prepare an effective vaccine for immunization and treatment of adults. Malaria killed more than 1 million people in 2006, most of them were children. We still do not have any vaccine effective in prevention of malaria; nevertheless, some vaccine candidates appeared and are now in Phase I or Phase II trial.
Keywords: financování organizované; Malaria Vaccines; Financing, Organized; vakcína proti malárii; Tuberculosis Vaccines; vakcíny proti AIDS; AIDS Vaccines; vakcíny proti tuberkulóze